Quality costs in construction: Case of Qom monorail project in Iran - Jafari, Amirhosein; Love, Peter (American Society of Civil Engineers, 2013)
The effectiveness of a quality program implemented during the initial 18 months of the Qom monorail project in Iran is examined. A quality costing exercise was undertaken, and it was revealed that quality failures accounted for 0.05% of the project's contract value. The contractor's experiences in implementing and analyzing its quality costs offer a learning opportunity for companies seeking a competitive advantage by implementing quality improvement programs.